Four-dimensional flow magnetic resonance imaging visualizes reverse vortex pattern and energy loss increase in left bundle branch block . Issue 8 (17th December 2021) - Miyajima, Keisuke; Urushida, Tsuyoshi; Ito, Kazuki; Kin, Fumihiko; Okazaki, Ayako; Takashima, Yasuyo; Watanabe, Tomoyuki; Kawaguchi, Yoshitaka; Wakabayashi, Yasushi; Takehara, Yasuo; Maekawa, Yuichiro
Abstract: Aims: This study aimed to investigate the intraventricular blood flow pattern of patients with left bundle branch block (LBBB) using four-dimensional flow magnetic resonance imaging (4D-flow MRI). Methods and results: We performed 4D-flow MRI for 16 LBBB patients (LBBB group) and 16 propensity score-matched patients with a normal QRS duration (non-LBBB group). The energy loss (EL) in the left ventricle was evaluated. In both groups, blood flow from the mitral valve to the apex of the heart and left ventricular (LV) outflow tract during LV diastole were observed. Vortices were also observed in both groups. There were two patterns of vortices: unidirectional clockwise rotation and counterclockwise rotation taking place from the mid-diastole to the systole (reverse pattern). The reverse pattern was observed significantly more frequently in the LBBB group (LBBB 94% vs. non-LBBB 19%, P < 0.001). The interobserver agreement for the streamline analysis was good (kappa = 0.68). The maximum EL was significantly higher in the LBBB group [LBBB 12 (11–15) mW vs. non-LBBB 8.0 (6.2–9.7) mW, P < 0.001]. Conclusion: Left bundle branch block patients may suffer from inefficient LV haemodynamics reflected by non-physiological counterclockwise vortices and increased EL. Thus, the shape of the vortices and EL in the left ventricle can serve as markers of LV mechanical dyssynchrony in LBBB patients and could be investigated as predictors of response to cardiac resynchronization therapy.